An overview of travel-associated central nervous system infectious diseases: risk assessment, general considerations and future directions - Morteza Izadi; Arman Is'haqi; Mohammad Ali Is'haqi; Nematollah Jonaidi Jafari; Fatemeh Rahamaty; Abdolali Banki (Asian Pacific Journal of Tropical Biomedicine, 2014)
Nervous system infections are among the most important diseases in travellers. Healthy travellers might be exposed to infectious agents of central nervous system, which may require in-patient care. Progressive course is not uncommon in this family of disorders and requires swift diagnosis. An overview of the available evidence in the field is, therefore, urgent to pave the way to increase the awareness of travel-medicine practitioners and highlights dark areas for future research. In November 2013, data were collected from PubMed, Scopus, and Web of Knowledge (1980 to 2013) including books, reviews, and peer-reviewed literature. Works pertained to pre-travel care, interventions, vaccinations related neurological infections were retrieved. Here we provide information on pre-travel care, vaccination, chronic nervous system disorders, and post-travel complications. Recommendations with regard to knowledge gaps, and state-of-the-art research are made. Given an increasing number of international travellers, novel dynamic ways are available for physicians to monitor spread of central nervous system infections. Newer research has made great progresses in developing newer medications, detecting the spread of infections and the public awareness. Despite an ongoing scientific discussion in the field of travel medicine, further research is required for vaccine development, state-of-the-art laboratory tests, and genetic engineering of vectors.